PENGEMBANGAN MODUL AJAR BERBASIS MOTIVASI MODEL ARCS PADA MATA PELAJARAN INFORMATIKA KELAS VIII SMPN 15 MALANG - Perdana, Sigit; Kartika Candra Kirana; Eko Tristyo Purwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to develop a Learning Module based on ARCS learning motivation model in informatics subjects for class VIII of junior high school. This study used a research and development method (Research and Development) with the ADDIE development model. The trial design used was a one-group pretest-posttest design. The results of the study showed that the learning module developed based on the ARCS model was categorized as very valid, with an average validation of construction experts and material experts obtained a percentage of 95.8% with a very valid category. In the effectiveness test of the learning module in the cognitive domain, there was an increase with an average gain value of 0.61, including the moderate category. So that the results of the validity and effectiveness test of the learning module, a conclusion was obtained that the development of a learning module based on ARCS motivation model in informatics subjects for class VIII of SMPN 15 Malang was declared feasible to use.